Unusual anatomy of maxillary central incisor with two roots - T S Ashwini Shivakumar; Saleem Makandar; Ajay Kadam (Dental Hypotheses, 2012)
Introduction: Knowledge of root canal morphology is essential for successful endodontic therapy. Failure to recognize unusual root canal anatomy may lead to unsuccessful endodontic treatment. Case Report: This case report describes the successful endodontic treatment of the maxillary central incisor with unusual anatomy of two roots and two root canals. A 23-year-old male patient was referred for dental consultation with discoloration of the maxillary right central incisor with periapical lesion, which revealed unusual anatomy of root on radiographic examination, and was confirmed upon exploration. Discussion: As described by Vertucci, the maxillary central incisor presents a single root and single root canal in 100% of the cases. However, few cases of maxillary central incisors with two canals were reported in the literature, most of which were associated with developmental anomalies like fusion, germination or dens invaginatus. Clinician should be aware of the unusual anatomical variations that should be detected by the different diagnostic resources available.